Antioxidant and Anticonvulsant Effects of Medicinal Herbs - Aldarmaa, J; Liu, J; Long, J; Nyamdalai, O; Ariunaa, J (Proceedings of the Mongolian Academy of Sciences, 2011)
This study examines the anticonvulsant profile of some medicinal plants (astragalus mongolicus, corydalis sibirica, scutellaria baicalensis and Chelidonium majus) and antioxidant effects of Astragalus mongolicus and Chelidonium majus. Astragalus mongolicus and Chelidonium majus extracts possessed a significant dose-dependent scavenging effect on hydroxyl and lipid radicals by an in vitro ESR technique. Astragalus mongolicus (150 and 300mg/kg) and Scutellaria baicalensis (150 and 300mg/kg) extracts had anticonvulsant activities in the Pentylenetetrazol (PTZ). Maximal Scutellaria baicalensis in a dose of 150 and 300mg/kg significantly shortened the latency period seizures in the maximal electroshock (MES). Corydalis sibirica (150mg/kg) and Chelidonium majus (150 and 300mg/kg) extracts didn't influence on latency period in the PTZ and MES models. All extracts improved losing memory by passive avoidance task (longterm memory) and significantly didn't influence on drinking punishment in the Vogel's test. DOI: http://dx.doi.org/10.5564/pmas.v0i4.37 Proceedings of the Mongolian Academy of Sciences 2007 No 4 pp.3-16